Development of Tobacco Processing Plant in Ljubuški (Bosnia And Herzegovina) (Proceedings of Faculty of Civil Engineering, 2021)
The tobacco processing plant complex in town of Ljubuški was built in stages from 1880 on due to the growing needs of the tobacco processing industry, which has been the main economic industry in Ljubuški area, as well as in the whole of Hercegovina because similar plants were founded in Čapljina, Široki brijeg, Grude, Čitluk, Trebinje and Stolac. In what was once the southern outskirts of Ljubuški, on a trapeze – shaped plot, in total 11 structures were situated. In the Austro-Hungarian phase five magazines were built – warehouses for tobacco and its further classification and processing, as well as one administrative building and one residential building for the purpose of accommodating management employees. During the period of the Kingdom of Yugoslavia additional two buildings were built in the northern part of the lot: a new warehouse and a new facility for tobacco fermentation, while the two remaining buildings were built after World War II. During the 1960s the warehouse buildings were connected with bridges on the first-floor level in order to facilitate tobacco transportation to the fermentation unit. The placing of this complex led to the development of area that represents today’s centre of Ljubuški. High quality of construction, the level of external space design and the mere size of the complex indicates its importance. This article aims to reveal the historical and architectural and urbanistic analysis of the complex in order to evaluate its architectural and urbanistic qualities, which can be used as a basis for further revitalization processes of this central urban space and could generate new urbanity for Ljubuški, but it can also be used as basis for developing analyses of the remaining tobacco processing plants in Hercegovina.
Keywords: tobacco processing plant; Ljubuški; Hercegovina